2017
DOI: 10.2147/ndt.s152194
|View full text |Cite
|
Sign up to set email alerts
|

The effect of demographic features on aortic arch anatomy and its role in the etiology of cerebrovascular disease

Abstract: PurposeThe aim of this study was to retrospectively evaluate the distribution of aortic arches, the relationship with demographic characteristics, and the results of carotid and vertebral artery stenting procedures in patients diagnosed with cerebrovascular disease through the intra-arterial digital subtraction angiography (DSA) technique.MethodsA retrospective examination was performed on 288 patients diagnosed with cerebrovascular disease, who underwent DSA in the Department of Neurology of Gaziantep Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…A study conducted in our country evaluated 270 patients with cerebral angiography and revealed type 1 arch structure in 195 (72.2%) patients, type 2 in 40 (14.8%) patients, and type 3 in 35 (13%) patients (9). Another study in our country by İnanç et al (8) examined 288 patients with cerebral angiography and revealed 175 (61%) patients with type 1, 99 (34%) with type 2, and 14 (5%) with type 3 arch structure. Unlike these studies, our study had a higher type 2 arch structure than the others due to the slightly low average age of our patients.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…A study conducted in our country evaluated 270 patients with cerebral angiography and revealed type 1 arch structure in 195 (72.2%) patients, type 2 in 40 (14.8%) patients, and type 3 in 35 (13%) patients (9). Another study in our country by İnanç et al (8) examined 288 patients with cerebral angiography and revealed 175 (61%) patients with type 1, 99 (34%) with type 2, and 14 (5%) with type 3 arch structure. Unlike these studies, our study had a higher type 2 arch structure than the others due to the slightly low average age of our patients.…”
Section: Discussionmentioning
confidence: 92%
“…A total of 207 patients underwent endovascular procedures with a mean age of 64.4±13 years. The NIHSS score was calculated as median at 15 (12)(13)(14)(15)(16)(17)(18)(19) (percentile 25-75) and the ASPECT score at first arrival was calculated as median at 9 (8,9,10). The IV r-tPA was administered to 36 (17.4%) patients before endovascular treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All humans are born with a type 1 (totally horizontal) AA [4][5][6][7]. With age, they develop a type 2 (moderately sloping) or a type 3 (severely sloping) AA [4][5][6][7]. Most patients with type 2 and type 3 AA are older and have LVH [2].…”
Section: Discussionmentioning
confidence: 99%